2018
DOI: 10.1002/jum.14844
|View full text |Cite
|
Sign up to set email alerts
|

Prescreening for Osteoporosis With Quantitative Ultrasound in Postmenopausal White Women

Abstract: Objectives Calcaneal quantitative ultrasound (QUS) is a readily accessible and radiation‐free alternative to dual‐energy x‐ray absorptiometry (DXA) for assessing bone mineral density (BMD). Results obtained from QUS measurement cannot directly be compared to DXA, since these techniques capture different bone‐specific parameters. To identify individuals who are likely to have osteoporosis by DXA, device‐specific thresholds have to be defined for QUS. This cross‐sectional study evaluated the accuracy of QUS to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
3
15
1
2
Order By: Relevance
“…On the other hand, QUS was not effective in identifying subjects with osteoporosis in the present study (Table 4). This observation is contradictory to earlier studies which reported a satisfactory performance of QUS (of different manufacturers) in identifying people with osteoporosis defined by T-score [21,39]. [41].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…On the other hand, QUS was not effective in identifying subjects with osteoporosis in the present study (Table 4). This observation is contradictory to earlier studies which reported a satisfactory performance of QUS (of different manufacturers) in identifying people with osteoporosis defined by T-score [21,39]. [41].…”
Section: Discussioncontrasting
confidence: 96%
“…Particularly, the performance of CM-200 in identifying subjects at risk of osteoporosis changed from ineffective to effective ( Table 5). Some of the previous studies have applied modified QUS T-score to determine the optimal performance of QUS in identifying subjects at risk of osteoporosis [21,[42][43][44]. Oral et al (2019) found that at the modified QUS T-scores of −1.68 and −1.53 for men (mean age: 57.8 ± 13.7 years) and women (mean age: 53.7 ± 11.9 years), respectively, the sensitivity and specificity values obtained were around 70% [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Based on the population data, investigators have found that -1.455 for the right QUS T score and -1.48 for the left QUS T score achieved adequate screening parameters to identify Osteoporosis. [25] Cutoff scores produced a sensitivity of 41% and a specificity of 86.6% for the right QUS T score and a sensitivity of 51.3% and a specificity of 83.3% for the left QUS T score. With a higher QUS T score cut-off of -1.25, sensitivity was higher at 80.4% with a specificity of 59.7% as seen in a study from China.…”
Section: Dual-energy X-ray Absorptiometrymentioning
confidence: 92%
“…Özerklik gibi grup haklarını teminat altına alan uygulamalar grubun içindeki farklılıkları bastıran bir niteliğe sahip olabilir. Grup içinde kendini farklı hisseden kişiler bakımından ayrımcı muamelenin söz konusu olması insan hakları koruma mekanizmalarının kendisinden beklenen amacı gerçekleştirememesi sonucunu doğurabilmektedir 61 . Alman azınlığın yoğun yaşadığı İtalya'nın Güney Tirol bölgesinde İtalyan etnik kökenine sahip kişilerin çok büyük kısmı Movimento Sociale Italiano adlı İtalyan Faşist partisine oy vermekte, bir kısmı da bölgeyi terk etmektedir 62 .…”
Section: Kolekti̇f Hak Kullanimi Bakimindanunclassified